1984
DOI: 10.1159/000145916
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Quantified Amounts of Increased Intermittent Compressive Forces for 30 and 60 Days on the Growth of Limb Bones in the Rat

Abstract: The purpose of this study was to subject groups of rats each to a specific 10% increase in body weight, to a maximum of a doubling of body weight, to study the effects of quantified, increased, intermittent, compressive forces on limb bone growth. Chronic centrifugation was employed. 21-day-old male Sprague-Dawley rats were used. After 30 and 60 days of centrifugation, the rats were killed. The humerus, radius, ulna, femur, and tibia were removed from each animal, cleared of all soft tissues, measured and weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
2

Year Published

1984
1984
2008
2008

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
3
9
2
Order By: Relevance
“…The studies in the literature on the effects of hypergravity on bone growth are consistent in using accelerations greater than 2.0 g and are also consistent in reporting a repression of bone growth with increased g values [Amtmann and Oyama, 1976;Briney and Wander, 1962;Smith, 1975Smith, , 1977a.m .o.]. However, when lambs were loaded by weights totaling 40% of total body weight, positive bone growth effects were reported [Tulloh and Romberg, 1963], The results of our first study using constant centrifu gation [Simon et al. 1984a] suggested that the value of g and the time spent at centrifugation are both significant factors in the effects of simulated increases in body weight on limb bone growth.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The studies in the literature on the effects of hypergravity on bone growth are consistent in using accelerations greater than 2.0 g and are also consistent in reporting a repression of bone growth with increased g values [Amtmann and Oyama, 1976;Briney and Wander, 1962;Smith, 1975Smith, , 1977a.m .o.]. However, when lambs were loaded by weights totaling 40% of total body weight, positive bone growth effects were reported [Tulloh and Romberg, 1963], The results of our first study using constant centrifu gation [Simon et al. 1984a] suggested that the value of g and the time spent at centrifugation are both significant factors in the effects of simulated increases in body weight on limb bone growth.…”
Section: Introductionsupporting
confidence: 77%
“…The data from our previous study [Simon et al, 1984a] on the effects of simulated increases in body weight on limb bone growth in weanling male rats sac rificed at 90 days of age suggested an inverse relation ship between increased g and bone growth. However, it would appear that if the animals are subjected to low levels of simulated increases of body weight from birth, acclimation is quickly achieved and the adolescent growth period is not disturbed detrimentally.…”
Section: Discussionmentioning
confidence: 88%
“…The limb bones from Sprague-Dawley male rats which had been used in our previous study [Simon et al, 1984a| were used for this investigation. In that study.…”
Section: The Animalsmentioning
confidence: 99%
“…Pioneering studies of artificial gravity performed during the early years of the manned space program studying artificial gravity showed that HG can alter the length and strength of bones in a variety of rapidly growing animals (1,14,21,28,34,40,49). Therefore, the purpose of the present study is to further explore the consequences of HG on musculoskeletal metabolism, particularly collagen catabolism and anabolism from mineralized and nonmineralized tissue structures.…”
mentioning
confidence: 97%
“…It is also known that many different physiological stimuli, such as physical, electrochemical, and hormonal stresses, collectively impact bone homeostasis in vivo and in vitro (43,46,47,50,51,52). In addition, the microgravity environment of space is known to induce significant alterations in bone structure and metabolism following acute spaceflight (11,28,30,40). Therefore, an alteration in the gravitational loading stress is an additional factor that affects the processes that govern the plasticity of the musculoskeletal system.…”
mentioning
confidence: 99%